Portrait of Lithuanian Striking Teachers - Žiliukaitė, Rūta; Stonkuvienė, Irena (Acta Paedagogica Vilnensia, 2024)
Teachers are one of the most frequent and largest groups of strikers in Lithuania. Using data from the four waves of Teachers‘ Civic Empowerment Index survey, the article aims to give individual level description of the teachers participating in the strikes in Lithuania. The results of the analysis show that teachers who participate in strikes have significantly stronger civic power in terms of civic activism and influence than teachers who do not participate in strikes. Cultural theories of political action, which emphasise the importance of pro-democratic value orientations, also are important explaining the behaviour of striking teachers.
Keywords: teachers; participation in strikes; civic power